The role of family factors on the relapse behavior of male adolescent opiate abusers in Kerman ( A Province in Iran). - Golestan, Samira; Abdullah, Haslinda; Ahmad, Nobaya; Anjomshoa, Ali (Canadian Center of Science and Education, 2010)
This study explores the significance of the family factors on drug use and its effects on relapse. In this respect, the effects of parental substance use, family conflict, and family structure are discussed in this research. The family, as a fundamental social unit of society, can be expected to exert remarkable influences on the development of social behaviors such as adolescent substance use and also relapse (Rouholamini, 2002). Since nearly 90% of drug abusers in Iran live with a family member (Mokri, 2002), therefore family has an important role to reduce the high rates of relapse after detoxification. Therefore, this study considers three factors: Parental substance use, Family Conflict, and Family Structure. The objective of this study is to examine the effects of family factors (Parental substance use, Family Conflict, and Family Structure) on relapse behavior among male adolescent opiate users in Kerman. In this research 226 adolescents between the ages of 13 to 20 were selected based on ten rehabilitation centers to answer the Self-administered questionnaire. Results showed that there were important relationships between these factors with relapse in adolescents. The study proposes some suggestions in order to prevent relapse after treatment in adolescents.